'Becoming animal': motifs of hybridity and liminality in fairy tales and selected contemporary artworks - Wasserman, Minke (Rhodes University, Faculty of Humanities, Department of Fine Art, 2015)
Becoming Animal': Motifs of Hybridity and Liminality in Fairy Tales and Selected Contemporary Artworks serves as a theoretical examination of the concept of the hybrid. My research unpacks the liminal aspect of hybridity, locating the hybrid in the imaginative world of popular fairy tales, folk lore and mythology. In my accompanying MFA exhibition, Becoming(s), I explore these motifs through an installation of mixed-media sculptures which are based on the hybrid creatures that populated the fantasy world of my childhood. The written component of my MFA submission will relate directly to my professional art practise, developing it further and situating it within a relevant context. In my mini-thesis I will consider the liminal in relation to the 'animal turn' in contemporary art, with a particular focus on relevant artists working with the motifs of hybridity, such as Nandipha Mntambo, Jane Alexander and Kiki Smith. The 'animal turn' is a term used by Kari Weil (2010: 3) to describe a contemporary interest in issues of the nonhuman, and in the ways that the relationship between humans and nonhumans is marked by "difference, otherness and power" . Of key concern to my research will be Giles Deleuze and Felix Guattari's concept of 'becoming animal'. Rather than describing a transition from one stable state to another, 'becoming animal' suggests a radical dissolution of boundaries "“ not just between species (such as 'human' and 'animal') but between any essentialising binaries. As such, 'becoming animal' suggests a conception of identity as being fluid and mutable, rather than stable and fixed.
Keywords: Fairy tales -- History and criticism; Liminality in literature; Cultural fusion in literature; Cultural fusion and the arts; Art, Modern -- 21st century -- Themes, motives; Art, Modern -- 21st century -- Exhibitions; Human-animal relationships in art; Human-animal relationships in literature